AReGeoDatHa: Apulian Regional GeoDatabase for geo-hydrological Hazards. (15th November 2022) - Vennari, Carmela; Salvati, Paola; Bianchi, Cinzia; Casarano, Domenico; Parise, Mario; Basso, Alessia; Marchesini, Ivan
Abstract: In many territories, geo-hydrological disasters represent a problem of considerable importance, given that they can cause substantial property damage, above all, life losses. In Italy, the geo-hydrological risk is widespread depending on the geomorphological settings, climate conditions and anthropic pressure. Accurate knowledge regarding the spatial and temporal extensions of past events, as well as the associated damages, allows the elaboration of hazard and risk maps. The resulting data are strongly dependent on the accuracy and efficiency of the sources used for data collection. In the framework of a long-term regional project, we compiled a geospatial database of geo-hydrological hazards and damage that occurred in the Apulian region of southern Italy over the last few decades. We used a validated database structure and improved it for practical and scientific purposes, thereby making it compliant with the needs of the stakeholders (i.e., regional civil protection agency) as it considers the regional geo-hydrological peculiarity and, at the same time, it follows the FLOOD and INSPIRE European directives. Based on the research and analysis of different information sources, we propose a method for quantitatively evaluating the availability, efficiency, and accuracy of each utilized source (i.e., source of information total quality index—SIQI) in an objective and reproducible manner. The SIQI index of the sources used is analyzed and discussed. We discuss the collected data on geo-hydrological processes and/or damage between 2008 and 2019, analyze their temporal and geographical distribution, and make comparisons with other national catalogues and daily geo-hydrological warning alerts. Graphical abstract: Image 1 Highlights: Research of geo-hydrological damaging events, at regional scale, is performed. A rigorous relational database structure is used and a web interface is designed for viewing and entering information. The temporal frequency and geographical persistency of the geo-hydrological events is evaluated. The results demonstrate an increase in frequency of damaging events in the last years. A "source of information quality index" (SIQI) is designed to evaluate in an objective and reproducible way the quality of the ty of information source used.